2014
DOI: 10.2136/sssaj2014.04.0176
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide and Nitrous Oxide Emissions Impacted by Bioenergy Sorghum Management

Abstract: Modern bioenergy feedstocks, such as bioenergy sorghum [Sorghum bicolor (L.) Moench], are being developed to supply future cellulosic biofuel demands. How these cropping systems impact greenhouse gas (GHG) emission of CO2 and N2O from the soil is unknown and field research is necessary to elucidate the effects of agronomic management practices on soil trace gas emissions. We studied the effects of N fertilization (0 vs. 280 kg urea‐N ha−1), residue management (0 vs. 50% of sorghum biomass returned), crop seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…This competition is intensified with the additional challenge of feeding an expected world population of 9 billion by the middle of this century [117,118]. One way to alleviate traditional versus bioenergy crop competition is to grow bioenergy crops during fallow periods that do not conflict with traditional crops.…”
Section: Other Considerationsmentioning
confidence: 99%
“…This competition is intensified with the additional challenge of feeding an expected world population of 9 billion by the middle of this century [117,118]. One way to alleviate traditional versus bioenergy crop competition is to grow bioenergy crops during fallow periods that do not conflict with traditional crops.…”
Section: Other Considerationsmentioning
confidence: 99%
“…Ramu et al (2012) reported greater N 2 O emissions from a welldrained Alfisol than from an adjacent poorly-drained Vertisol, demonstrating that factors other than drainage can affect cumulative N 2 O emitted. Soil N 2 O emissions from N-fertilised sorghum in tropical and sub-tropical regions have been reported from Oxisols (Mosier et al 1998;De Antoni Migliorati et al 2015) an Inceptisol (Storlien et al 2014), an Entisol (Welzmiller et al 2008) and an Alfisol (Ramu et al 2012), but only Ramu et al (2012) has documented N 2 O emissions from a Vertisol in central India. The potential for denitrification losses of N as N 2 O and N 2 is high, particularly if high intensity rainfall occurs early in the growing season (Schwenke et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the warm climate also increases soil GHG emissions (Xu & Luo, 2012). Therefore, production of biofuel crops will compromise the main goal of biofuel production if it increases the net GHG emissions (Storlien, Hons, Wight, & Heilman, 2014). Apart from the climate, soil GHG emissions are affected by different agronomic practices (Adviento-Borbe, Haddix, Binder, Walters, & Dobermann, 2007), such as tillage, crop rotation, fertilization, residues return, and irrigation.…”
Section: Impact Of Ca On Soil Ghg Emissionsmentioning
confidence: 99%
“…Crop residue retention increased CO 2 emissions compared with treatments where residues are removed (Dendooven et al, 2012;Storlien et al, 2014). Storlien et al (2014) conducted a study using two levels of residue retention, 0% and 50%, along with fertilization under bioenergy sorghum production, and reported that 50% residue retention increased CO 2 by 12% compared with treatments without residue retention. Crop residues are a source of carbon which can increase microbial activities (Ussiri & Lal, 2009) and that is the reason why their retention increased CO 2 .…”
Section: Impact Of Ca On Soil Ghg Emissionsmentioning
confidence: 99%